2005
DOI: 10.1016/j.febslet.2004.11.114
|View full text |Cite
|
Sign up to set email alerts
|

1.15 Å Crystal structure of the X. tropicalis Spred1 EVH1 domain suggests a fourth distinct peptide‐binding mechanism within the EVH1 family

Abstract: Edited by Hans Eklund Abstract The recently described Spred protein family has been implicated in the modulation of receptor tyrosine kinase signalling. We report the crystal structure of the Enabled/vasodilator-stimulated phosphoprotein homology-1 (EVH1) domain from Xenopus tropicalis Spred1, solved to 1.15 Å resolution. This structure confirms that the Spred EVH1 adopts the pleckstrin-homology fold, with a similar secondary structure to Enabled. A translation of one of the peptide-binding groove bstrands nar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 31 publications
2
21
0
Order By: Relevance
“…The crystal structure of the Xenopus tropicalis Spred1 EVH1 domain suggests a distinct peptide-binding mechanism compared with other identified EVH1 domains (Harmer et al 2005). Although an interacting protein for the Spred2 EVH1 domain has recently been reported (NBR1) (Mardakheh et al 2009), proteins that specifically interact with the Spred1 EVH1 domain have yet to be determined.…”
Section: Resultsmentioning
confidence: 99%
“…The crystal structure of the Xenopus tropicalis Spred1 EVH1 domain suggests a distinct peptide-binding mechanism compared with other identified EVH1 domains (Harmer et al 2005). Although an interacting protein for the Spred2 EVH1 domain has recently been reported (NBR1) (Mardakheh et al 2009), proteins that specifically interact with the Spred1 EVH1 domain have yet to be determined.…”
Section: Resultsmentioning
confidence: 99%
“…The SPRED1 EVH-l domain has been suggested to bind to a ligand in a groove formed by ␤-strands ␤l, ␤2, ␤6, and ␤7 (38). Missense mutations with a severe effect on GRD binding such as G30R, W31C/W31L, V44D, G62R, G100D, and T102K/ T102R are probably present in the groove for the binding to the GRD or important for the structure of the binding groove.…”
Section: Evh1 Missense Mutations Found In Legius Syndromementioning
confidence: 99%
“…Recently, structural information on the Spred EVH1 domain revealed that this domain adopts, like the other EVH1 domains, a pleckstrin homology fold (48,49). However, for the Spred EVH1 domain a different induced fit peptide binding mechanism has been proposed even in the absence of a characterized ligand for this domain (48,49), which makes the identification of binding partners a point of major interest (Fig. 1).…”
Section: Domains: Structure and Functionsmentioning
confidence: 99%